An unusual case of vaginal myoma presenting with postmenopausal bleeding. - Lajya Devi Goyal; Harpreet Kaur; Kanwardeep Kaur; Sharanjit Kaur (Tehran University of Medical Sciences, 2013)
Vaginal leiomyomas are uncommon benign tumour with variable clinical presentation. These tumours arise most commonly from anterior vaginal wall. We report a case of 50-year old postmenopausal woman who presented with urinary retention, profuse vaginal bleeding and mass protruding into vagina. Local examination revealed a pedunculated mass attached to the posterior vaginal wall with vascular stalk one cm below the cervix. Mass was hanging outside vulva and vascular pedicle was profusely bleeding. The pedicle was ligated and tumour was excised. Subsequent histopathology revealed a vaginal myoma.